AN ANALYSIS OF TENTH GRADE STUDENTS’ DIFFICULTIES IN WRITING PROCEDURE TEXT - Suci Wahyuning Tiyas; Dina Kartikawati (Media Inovasi Pendidikan dan Publikasi, 2024)
Writing is an important aspect of language learning. The process can be somewhat complicated, particulars for non-native speakers. Based on this background, the purpose of this study is to find out the difficulties faced by tenth grade students in writing procedure text and to find out the factors that cause tenth grade students to have difficulty in writing procedure text. This method is a qualitative research. The subject of this study were 27 tenth grade students. The results showed that 5 students did not focus on the topic, 12 students had difficulty in word selection, 10 students had difficulty with the use of conjugations, 3 students had difficulty with the use of imperative sentences, 7 students had difficulty with sentence structure, and 6 students had difficulty with the use of punctuation. The factors that cause students’ difficulties in writing procedure text are lack of knowledge, self-confidence, translating Indonesia into English.